Unusual occurrences of fishes along the Northeast Atlantic: new biological and distributional data - BAÑÓN, RAFAEL; TEJERINA, RAQUEL; MORALES, XESÚS; ALONSO-FERNÁNDEZ, ALEXANDRE; BARROS-GARCÍA, DAVID; DE CARLOS, ALEJANDRO (Mediterranean Marine Science, 2019)
The occurrences of 13 specimens belonging to 9 species of little known marine fishes in the Northeast Atlantic in 2017 and 2018 are reported. Information about the morphology and new findings of Decapterus tabl and Decapterus macarellus (Carangidae), Kyphosus vaigiensis (Kyphosidae), Remora osteochir (Echeneidae), Antigonia capros (Caproidae), Hyperoglyphe perciformis (Centrolophidae), Halobatrachus didactylus (Batrachoididae), Parapristipoma octolineatum (Haemulidae) and Zu cristatus (Trachypteridae) are reported in different locations, where they are categorized as unusual or rare. Morphometric and meristic parameters confirm the identification to species level of each specimen, also supported by DNA barcoding. Histological examination of reproductive tissue is carried out in four specimens to know the sex and their reproductive stage. All species are known from other areas of the Atlantic Ocean, but these findings are an important contribution to understanding their biology and distribution. These include a new northernmost record of Remora osteochir and Decapterus tabl in the eastern Atlantic and the first records of Antigonia capros, Hyperoglyphe perciformis, Halobatrachus didactylus and Parapristipoma octolineatum from Galician waters.